PROSES PEMBUATAN LOWER MOUNTING CYILINDER DENGAN MATERIAL S45C DI CV. SUTECHINDO JAYA PRESISI - Eko Aprianto Nugroho; Abdul Rahman Agung Ramadhan (Asosiasi Dosen Muda Indonesia, 2024)
The lower mounting cylinder is a spare part for the hydraulic scissor lift. Where the lower mounting cylinder acts as the lower hydraulic cylinder holder. Where the lower mounting cylinder is one of the important spare parts of the scissor lift. The purpose of this paper is to understand the manufacturing process, understand the types of materials used in the manufacturing process, understand product functions, and The formula for calculating the spindle acceleration of lathes and milling machines in the lower mounting cylinder manufacturing process. In the lower mounting cylinder manufacturing process, S45C carbon steel is used, including medium quality steel. In the lower mounting cylinder manufacturing process, materials are prepared, material is cut, and turning. first, the milling process, the scrap process, the second turning process, the tap process and quality control. Where is the S45C material preparation, then the first turning uses cylindrical and chamfering, then milling which creates a barrier during the scrap process, then the scrap process which changes the diameter of the workpiece to square, then the drilling process, namely punching holes in the workpiece, then the second turning process, namely boring and chamfering, then the tap process, namely the threading process in the lubricant path and quality control, namely product checking. in the milling process, the spindle speed is 663.481Rpm. Before the lower mounting cylinder is packed, a check will be carried out on the workpiece to find out whether it is feasible and the size is appropriate or not. If the workpiece is deemed fit, it will be packaged for marketing, if not, the workpiece will be destroyed.